Edukasi Masyarakat Cermat terhadap Iklan dan Promosi Obat Tradisional di Desa Penyengat Olak Kabupaten Muara Jambi - Haflin Haflin (Jurnal Abdimas Kesehatan (JAK), 2020)
Advances in technology and the increasing desire of the community to use traditional medicines, traditional medicines are no longer used as ingredients for family consumption, but have become merchandise. Advertising is a way for corporate producers to promote their products, especially traditional medicines. The POM RI released 76% of advertisements for traditional medicines that did not comply with The Regulation. In order to protect the public against the possibility of distributing drugs and traditional medicines that do not meet the requirements due to false advertising and information, it is necessary to educate the public to increase public knowledge and understanding of traditional medicines and medicines. Penyengat Olak village, Muara Jambi district is one of the partners of the Ministry of Health's Jambi Poltekes whose community has never been educated on traditional medicinal advertisements. The implementation method used is survey, observation, interview, discussion, question and answer, and evaluation. This community service activity was attended by 20 people. The result of this activity is an increase in public knowledge and understanding of the correct traditional medicinal advertisements so that people can be more careful and careful in choosing traditional medicinal products, and do not easily believe in incorrect advertisements, and the use of family medicinal plants in the environment around the house. , all participants attended health education from start to finish and most of them actively participated during the activity. It is recommended that the community is always communicative with local health workers to understand the treatment being carried out, and to increase the role of health workers in collaboration with district health offices to provide information, especially related to traditional medicinal advertisements